Investigation of magneto-structural phase transition in FeRh by reflectivity and transmittance measurements in visible and near-infrared spectral region. (3rd August 2016) - Saidl, V; Brajer, M; Horák, L; Reichlová, H; Výborný, K; Veis, M; Janda, T; Trojánek, F; Maryško, M; Fina, I; Marti, X; Jungwirth, T; et al.
Abstract: Magneto-structural phase transition in FeRh epitaxial layers was studied optically. It is shown that the transition between the low-temperature antiferromagnetic phase and the high-temperature ferromagnetic phase is accompanied by a rather large change of the optical response in the visible and near-infrared spectral ranges. This change is consistent with ab initio calculations of reflectivity and transmittance. Phase transition temperatures in a series of FeRh films with thicknesses ranging from 6 to 100 nm is measured thereby demonstrating the utility of the method to quickly characterise samples. Spatially resolved imaging of their magnetic properties with a micrometer resolution shows that the phase transition occurs at different temperatures in different parts of the sample.